A Comprehensive Analysis of the Radiographic Characteristics and Bilateral Symmetry of the Mental Foramen - Radhwan Algabri; Faisal Abulohoom; Abdelrahman Fadag; Hesham Al‐Sharani; Sami Al‐Aqab; Nassr Al‐Hutbany; Emad Alryashi; Ahmed Keshk; Ahmed Yaseen Alqutaibi (Clinical and Experimental Dental Research)
ABSTRACT Objectives There is currently a scarcity of data on the frequency and bilateral symmetry of the position and other characteristics of the mental foramen (MF) and accessory mental foramina in Yemen. The objective of this study was to analyze the position and other characteristics, as well as the symmetry of the MF, in a sample of the Yemeni population. Materials and Methods A retrospective analysis was conducted on a sample of 500 digital panoramic radiographs (1000 sides). The study examined various characteristics of the MF, including horizontal and vertical positions, shapes, appearances, and the presence of accessory mental foramina. Additionally, the study explored potential associations between these characteristics and variables such as the subject's gender, sides, and symmetry. Data analysis was performed using SPSS, and statistical significance was evaluated using chi‐square tests; the p value was set at 0.05. Results The horizontal position of the MF was most frequently observed between the first and second lower premolars (63.2%). The vertical position of the MF was predominantly below the apices of the lower premolars (66.2%). The majority of MFs had a round shape (46.3%). In 72% and 75.6% of cases, there was a continuous and descending relationship between the MF and the mandibular canal, respectively. Accessory mental foramina was present in 3.8% of cases. Gender differences were significant for the shape of the MF and the pattern of the canal on the right side. The symmetry rates for various features included horizontal positions (87.4%), vertical positions (82.6%), and shapes (80.4%). Conclusion The MF is most commonly situated horizontally between the lower premolars and vertically below the apices of these teeth. The majority of MFs showed a round shape and a continuous and descending relationship with the mandibular canal. In most instances, characteristics of the MF were symmetrical on both sides.